Behavior Analysis of Social Media Use Among Adolescents - Nugraha, Ardi Maulana; Ichsan, Ichsan; Ningtyas, Mustika Wati Alfia; Arief, Abdul Samad; Cakranegara, Pandu adi (Sinkron : jurnal dan penelitian teknik informatika, 2022)
This study intends to find out how the influence of adolescent behavior on social media users. Currently, almost the majority of teenagers in Indonesia use social media. Social media is something that cannot be left behind in the daily life of teenagers. Researchers, in this case, analyze the behavior of teenagers in using social media. used in this research. This research is included in quantitative research with data collection methods through observation, interviews, and questionnaires. The data analysis method used is the normality test, linearity test, simple linear regression coefficient test, and hypothesis testing using determination test or R2. Sampling in this study using a proportional random sampling technique. The number of samples obtained as many as 40 respondents with the criteria of teenagers who access social media Facebook. Research results based on the results of research and discussion of the influence of Facebook media on behavioral deviations in adolescents, it can be concluded that there is a significant influence between the use of Facebook media on behavioral deviations of adolescents who includes the words of students can be seen from the words of students who are not polite, the use of dirty words in daily communication. Students' addiction to Facebook makes students tend to use Facebook whenever and wherever there is an opportunity, even during lessons. Students' individualism can be seen from the use of Facebook to communicate and rarely meet directly with friends which results in a decrease in social attitudes in students who tend not to care about the surrounding environment.